Analysis of the Work of Foreign Researchers on the Prevention of Typical Errors made by Students - Ashirbayev , Azim (Рroblems of engineering and professional education, 2024)
The article reviews the theoretical literature on the issue of the occurrence and causes of errors in learning, identifies the types of errors. The author analyzes studies on typical errors made by students when mastering geometric problems. This article investigates how foreign researchers, including Schleppenbach and others, examine student errors in classroom settings. A key comparison is made between Chinese and American teachers, revealing different approaches: American teachers often hide or avoid discussing student mistakes, while Chinese teachers encourage students to reflect on their errors conceptually. This reflective process is essential for students to develop a deeper understanding of the material. Ball emphasizes that teachers should use mistakes as a learning tool, delving beyond simple "right or wrong" analyses. Newman’s error analysis also plays a crucial role, highlighting stages where students encounter difficulties— reading, comprehension, transformation, and processing. The study also emphasizes spatial intelligence, including skills like spatial perception, mental rotation, and visualization, to assess how students solve geometric problems. Understanding the types of errors, such as procedural or encoding mistakes, is essential for improving teaching methods. Furthermore, researchers like Jacobs and Ambrose suggest that teachers can guide students to think critically about their mistakes, allowing them to correct misconceptions.